Butehamun and the God’s Wife of Amun Maatkare Mutemhat: Two Problematic Burials - Thijs, Ad (Zeitschrift für ägyptische Sprache und Altertumskunde, 2020)
In this article it is argued that the traditional view concerning the Gods Wife of Amun Maatkare is untenable. It is impossible to square the date of her coffins with her appearance as a young girl during the reign of Smendes. In 1984 A. Niwiński published an article in which he postulated the existence of no less than three scribes called Butehamun. Although his hypothesis was very soon afterwards falsified, the problems with the funeral equipment of Butehamun which led him to his remarkable theory have never been adequately dealt with. Like Maatkare, Butehamun himself is dated to the start of the 21 st Dynasty, whereas his coffins point towards a much later date. For both problems an alternative solution is proposed.